PROGRAM LITERASI KESEHATAN GIGI DAN MULUT MELALUI KUIS INTERAKTIF TENTANG KEGOYANGAN GIGI PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS MARGASARI, TEGAL - Poetri, Adisty Restu; Novianti, Shella Indri; Mayangsari, Regilia Shinta; Yuniar, Savira Nurazky; Indrawati, Silvia Vera; Dimas P. P., Muhammad (Faculty of Dentistry Universitas Islam Sultan Agung, 2023)
Background: Oral health is an important part of an individual's overall health. The presence of disorders of the oral cavity can significantly affect a person's life. One of the problems that often arise is loose teeth. Loose teeth can be caused by disease or injury to the gums and the supporting tissues of the teeth. The most common factor that causes loose teeth is the buildup of plaque or tartar. This condition can cause damage to the bone that supports the teeth and the periodontal ligament which causes the teeth to become loose. In addition, a person's systemic conditions such as diabetes mellitus also aggravate the condition of tooth mobility. Method: This community service is carried out by counseling, distributing leaflets, poster, quiz, and giving door prizes. The audience's level of knowledge related to dental and oral health, especially periodontal tissue was evaluated using a questionnaire Result: 1 respondent (3.33%) had low oral hygiene habits, 24 respondents (83.3%) had moderate oral hygiene habits, and 4 respondents (13.3%) had very good/high oral hygiene habits. Conclusion: Dental and oral health education in the community can effectively improve oral hygiene